The Islamist mafias: a new perspective for the study of the crime terror nexus - Pollichieni, Luciano (2021)
The aim of this thesis is to introduce a new paradigm for the study of the crime terror nexus: the one of the “Islamist Mafias”. The “Islamist Mafias” are criminal organizations, which use violence and religion in order to achieve the enrichment of their members in terms of power and money. In the development of this work, two case studies will be examined to introduce and illustrate this paradigm: the Sahelian Jihadi Groups and the Haqqani Network.